2005
DOI: 10.1021/ic0502168
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Bridged Borate Anions from Tris(pentafluorophenyl)borane:  Synthesis, NMR Characterization, and Reactivity

Abstract: The previously known anion [(C6F5)3B(mu-OH)B(C6F5)3]- (2) has been prepared by a two-step procedure, involving deprotonation of (C6F5)3BOH2 to give [B(C6F5)3OH]- (1), followed by addition of B(C6F5)3. The solution structure and the dynamics of 2 have been investigated by 1H and 19F NMR spectroscopy. The reaction of [NHEt3]2 with NEt3 resulted in the formation of [NHEt3]+ [(C6F5)3BOH]-, [NHEt3]+ [(C6F5)3BH]-, and (C6F5)3B- (CH2CH=N+ Et2). This indicates that in the presence of a nucleophile anion 2 can dissocia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
84
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 45 publications
4
84
1
Order By: Relevance
“…[10] The 1 H NMR (C 7 D 8 ) spectrum of 2 reveals a ca. 2 ppm downfield shift of the NH 2 protons relative to 1 and also displays a septet resonance at 8.24 ppm (J HF = 2 Hz), consistent with a H…F interaction between the formate proton and each of the six ortho-F's of the B(C 6 F 5 ) 3 unit; this assignment was confirmed through selective heteronuclear 19 F decoupling experiments.…”
mentioning
confidence: 62%
See 3 more Smart Citations
“…[10] The 1 H NMR (C 7 D 8 ) spectrum of 2 reveals a ca. 2 ppm downfield shift of the NH 2 protons relative to 1 and also displays a septet resonance at 8.24 ppm (J HF = 2 Hz), consistent with a H…F interaction between the formate proton and each of the six ortho-F's of the B(C 6 F 5 ) 3 unit; this assignment was confirmed through selective heteronuclear 19 F decoupling experiments.…”
mentioning
confidence: 62%
“…[9] We have found that admission of CO 2 to a toluene solution of 1 at 100°C produces the unique formato-borate complex [TMPH][HCO 2 B(C 6 F 5 ) 3 ] (2) in quantitative yield; the reaction can be conveniently monitored using solution 19 F NMR. [10] The 1 H NMR (C 7 D 8 ) spectrum of 2 reveals a ca.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[15][16][17][18][19][20] In scattered examples, bulky amines have been shown to act as hydride donors [21] in reactions with BA C H T U N G T R E N N U N G (C 6 F 5 ) 3 via a C À H activation alpha to nitrogen [Eqs. (1)(2)(3)].…”
Section: Introductionmentioning
confidence: 99%